New Dimensions of Islamic Theory of Ethical Behaviour: An Empirical Investigation - Hanudin Amin (Bank Indonesia, 2025)
This study examines factors that explain ethical behaviours of young lecturers in two Malaysian universities. To this end, we develop an Islamic theory of ethical behaviour (ITEB) incorporating piety, vicegerency, accountability, ethical behaviour and religious satisfaction as key factors, the measurements of which are validated by Shariah scholars, and apply the theory to a sample of 496 young lecturers. Employing Partial Least Squares – Structural Equation Modelling (PLS-SEM) with SmartPLS4.0 software, we reach the conclusion that all ITEB factors are significantly related to the ethical behaviour. Among them, vicegerency is likely the strongest driver of ethical behaviour, followed by accountability and piety. Ethical behaviour and religious satisfaction are also significantly related. This study offers the ITEB as a meaningful framework for upstanding ethical conducts through the lens of young lecturers. Acknowledgment This write-up is funded by Islamic Economics Research and Innovation Fund (IERIF) 2024, INCEIF University, ISRA Research Management Centre (ISRARMC/IERIF/AWARD/2024/BATCH 1/63), Malaysia.